Perubahan Iklim, Sustainable Land Management dan Responsible Land Governance - Pinuji, Sukmo (BHUMI: Jurnal Agraria dan Pertanahan, 2020)
Climate change has become a global challenge affecting almost all aspects, including land management. In sustainable development goals, land management play role in 5 goals related to land. Land management paradigm, an aggregation of land policy function, and administration function (land tenure, value, use, and development), and land information infrastructure, play important roles in developing land management system adaptive to climate change. In the context of good land governance, this paper describes the roles of land administration in an attempt to build adaptive and resilient land management on climate change, including challenges that are particularly faced by developing countries. Some key points on the integration including (i) land policy formulation that affiliates climate change, including planning, implementation, and monitoring evaluation, affiliating vulnerable, minority and specific gender community and involving all key stakeholder; (ii) land right protection, including access to land and natural resources, with balance function of its tenure, value, use and development, and (iii) available land information infrastructure as a tool for spatial-based decision making. Keywords: sustainable development goals, land management, land governance, climate change. Intisari: Perubahan iklim telah menjadi tantangan global yang mempengaruhi hampir semua lini kehidupan, termasuk dalam manajemen pertanahan. Dalam tujuan pembangunan berkelanjutan, manajemen pertanahan memegang setidaknya 5 (lima) tujuan utama yang berkaitan dengan pertanahan. Paradigma manajemen pertanahan yang merupakan kesatuan dari fungsi kebijakan pertanahan, administrasi pertanahan (land tenure, value, use dan development) serta fungsi infrastruktur informasi pertanahan memegang peranan penting dalam menciptakan manajamen pertanahan yang adaptif terhadap perubahan iklim. Dalam kerangka tata kelola pertanahan, makalah ini mendeskripsikan peran administrasi pertanahan dalam menghadapi tantangan perubahan iklim, serta tantangan-tantangan yang dihadapi, utamanya di negara berkembang. Beberapa poin utama tersebut diantaranya adalah (i) rumusan kebijakan pertanahan yang mengafiliasi perubahan iklim, yang meliputi perencanaan, penerapan dan pemantauan evaluasi yang mampu mengafiliasi kelompok rentan, minoritas dan gender tertentu serta melibatkan seluruh stakeholder kunci; (ii) perlindungan terhadap hak atas kepemilikan tanah dan akses terhadap tanah dan sumberdaya yang berimbang antara fungsi land tenure, value, use dan development, dan (iii) tersedianya infrastruktur informasi pertanahan yang dapat digunakan sebagai alat pengambilan keputusan. Kata Kunci: tujuan pembangunan berkelanjutan, manajemen pertanahan, tata kelola pertanahan, perubahan iklim